Accounting for the effects of AIDS on growth in Sub-Saharan Africa - (:unkn) unknown (My University, 2011)
In this paper, we first, perform a quantitative assessment of the impact of the HIV/AIDS epidemic on growth. Second, we precisely account for the effects of the epidemic on income per capita through human and physical capital accumulations, population and labor force. That is, we disentangle the effect on the different sources of short and long run growth. Using a dynamic panel of 46 Sub-Saharan African countries over the period 1981-2007, we show that HIV/AIDS has negative, significant and long-lasting effects on demography and growth. According to the estimates presented, GDP per working age population will be 12% lower in the long-run for the average African country than it should be if the epidemic had not spread out. However, the impact is huge for the countries experiencing a high prevalence rate. To tackle the endogeneity issue of HIV/AIDS, we provide a new series of HIV prevalence rate build from the estimation of the propagation dynamic of the epidemic.
Keywords: African Research